Triassic pentadactyl tracks from the Los Menucos Group (Río Negro province, Patagonia Argentina): possible constraints on the autopodial posture of Gondwanan trackmakers - Paolo Citton; Ignacio Díaz-Martínez; Silvina de Valais; Carlos Cónsole-Gonella (PeerJ, 2018)
The Los Menucos locality in Patagonia, Argentina, bears a well-known ichnofauna mostly documented by small therapsid footprints. Within this ichnofauna, large pentadactyl footprints are also represented but to date were relatively underinvestigated. These footprints are here analyzed and discussed based on palaeobiological indications (i.e., trackmaker identification). High resolution digital photogrammetry method was performed to achieve a more objective representation of footprint three-dimensional morphologies. The footprints under study are compared with Pentasauropus from the Upper Triassic lower Elliot Formation (Stormberg Group) of the Karoo Basin (Lesotho, southern Africa). Some track features suggest a therapsid-grade synapsid as the potential trackmaker, to be sought among anomodont dicynodonts (probably Kannemeyeriiformes). While the interpretation of limb posture in the producer of Pentasauropus tracks from the Los Menucos locality agrees with those described from the dicynodont body fossil record, the autopodial posture does not completely agree. The relative distance between the impression of the digital (ungual) bases and the distal edge of the pad trace characterizing the studied tracks likely indicates a subunguligrade foot posture (i.e., standing on the last and penultimate phalanges) in static stance, but plantiportal (i.e., the whole foot skeleton and related soft tissues are weight-bearing) during the dynamics of locomotion. The reconstructed posture might have implied an arched configuration of the articulated metapodials and at least of the proximal phalanges, as well as little movement capabilities of the metapodials. Usually, a subunguligrade-plantiportal autopod has been described for gigantic animals (over six hundreds kilograms of body weight) to obtain an efficient management of body weight. Nevertheless, this kind of autopod is described here for large but not gigantic animals, as the putative trackmakers of Pentasauropus were. This attribution implies that such an autopodial structure was promoted independently from the body size in the putative trackmakers. From an evolutionary point of view, subunguligrade-plantiportal autopods not necessarily must be related with an increase in body size, but rather the increase in body size requires a subunguligrade or unguligrade, plantiportal foot. Chronostratigraphically, Pentasauropus was reported from Upper Triassic deposits of South Africa and United States, and from late Middle Triassic and Upper Triassic deposits of Argentina. Based on the stratigraphic distribution of the ichnogenus currently accepted, a Late Triassic age is here proposed for the Pentasauropus-bearing levels of the Los Menucos Group.